Confined to Stay: Natural Disasters and Indonesia's Migration Ban - Andrea Cinque; Lennart Reiners (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the effects of international migration restrictions on communities' capacity to absorb income shocks after natural catastrophes. We adopt the implementation of an emigration ban on female Indonesians as a natural experiment. After an array of violent assaults against female servants in Saudi Arabia, the Indonesian government issued a moratorium in 2011, preventing millions of female workers to migrate there as domestic workers. Exploiting the exogenous timing of the ban and that of natural disasters allows us to estimate the causal effect of the absence of international migration as an adaptive strategy. Relying on a panel of the universe of Indonesian villages, we use a triple difference strategy to compare poverty levels in the aftermath of natural disasters for villages whose main destination is Saudi Arabia against others, before and after the policy shock. We find that in villages with strong ex-ante propensity to migrate to Saudi Arabia, poverty increases by 13% in face of natural disasters after the ban, further aggravating the already severe consequences induced by those events.
Keywords: F22; J61; Q54; 330; migration; natural disasters; Indonesia; migration ban